Model optimalisasi peran Ketua Rukun Tetangga dalam mencegah perceraian - Dyah Retna Puspita; Pawrtha Dharma; Rukna Idanati (Faculty of Social and Political Science, Universitas Airlangga, 2016)
The rising number of divorce in Purbalingga encourages the idea to optimize the divorce prevention effort by conducting family resilience counsulting. The target is neighbourhood association whose members are mostly men. Approach to them are necessary because they were rarely became the target of family counseling. As a social organization, activities within neighbourhood association are highly depends on its chairman. This research analyzes (1) neighbourhood association chairman's view regarding the divorces phenomena in Purbalingga Regency and (2) their roles in prevent divorces in their area. This research was conducted in District of Purbalingga which has high number of divorce cases. Sample locations for this research consist of four urban areas which purposively selected using chairman as responden. Data obtained through questionnaires and discussion groups, analyzed by simple quantitative techniques. The study shows that, firstly, most of respondents are lacking of awareness of the divorces phenomena in Purbalingga regency. This is because the association never receives the information or report of divorces. Second, there are several respondents that reported their cases to chairmen, but most of chairmen did not have the power to prevent it, because people who asked for divorce administration letter had their final decision to separate with their partner. Results lead to conclusion that the effort to decrease the number of divorce can be held by giving continual consultation to men about family resilience.